The Effects of Tuition Fees on Transition from High School to University in Germany - Kerstin Bruckmeier; Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies whether the introduction of tuition fees at public universities in some German states had a negative effect on enrollment, i.e., on the transition of high school graduates to public universities in Germany. In contrast to recent studies, we do not find a significant effect on aggregate enrollment rates. Our study differs from previous studies in three important ways. First, we take full account of the fact that tuition fees were both introduced and abolished in the German states at different points in time. Second, we consider control variables, which are absent in previous studies but turn out to have a significant impact on the evolution of enrollment rates. Third, we allow for state-specific effects of tuition fees on enrollment rates. We conclude that there is no evidence for a general negative effect of the recent introduction of tuition fees on enrollment in Germany.
Keywords: H75; I22; I28; 330; tuition fees; enrollment rates; treatment effect